Association of novel DNAH11 variants with asthenoteratozoospermia lead to male infertility - Senzhao Guo; Dongdong Tang; Yuge Chen; Hui Yu; Meng Gu; Hao Geng; Jiajun Fang; Baoyan Wu; Lewen Ruan; Kuokuo Li; Chuan Xu; Yang Gao; et al. (Human Genomics, 2024)
Abstract Background Bi-allelic variants in DNAH11 have been identified as causative factors in Primary Ciliary Dyskinesia, leading to abnormal respiratory cilia. Nonetheless, the specific impact of these variants on human sperm flagellar and their involvement in male infertility remain largely unknown. Methods A collaborative effort involving two Chinese reproductive centers conducted a study with 975 unrelated infertile men. Whole-exome sequencing was employed for variant screening, and Sanger sequencing confirmed the identified variants. Morphological and ultrastructural analyses of sperm were conducted using Scanning Electron Microscopy and Transmission Electron Microscopy. Western Blot Analysis and Immunofluorescence Analysis were utilized to assess protein levels and localization. ICSI was performed to evaluate its efficacy in achieving favorable pregnancy outcomes for individuals with DNAH11 variants. Results In this study, we identified seven novel variants in the DNAH11 gene in four asthenoteratozoospermia subjects. These variants led the absence of DNAH11 proteins and ultrastructure defects in sperm flagella, particularly affecting the outer dynein arms (ODAs) and adjacent structures. The levels of ODA protein DNAI2 and axoneme related proteins were down regulated, instead of inner dynein arms (IDA) proteins DNAH1 and DNAH6. Two out of four individuals with DNAH11 variants achieved clinical pregnancies through ICSI. The findings confirm the association between male infertility and bi-allelic deleterious variants in DNAH11, resulting in the aberrant assembly of sperm flagella and contributing to asthenoteratozoospermia. Importantly, ICSI emerges as an effective intervention for overcoming reproductive challenges caused by DNAH11 gene variants.